INTERAKSI VIRTUAL DALAM AKUN @tempodotco DALAM MERESPON TEROR TAHUN 2025 - AL KAUTSAR, AHMAD; Mahdinar; Tanjung, Alma Zahra; Muksin, Nani Nurani (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2025)
This study focuses on analyzing virtual interactions that occurred on the Instagram account @tempodotco in response to the terror experienced by Tempo in 2025. Using qualitative methods and a netnographic approach, this study collected and categorized thousands of comments, likes, and re-shared content activities on Instagram reels related to the incident of sending pig heads and dead rats. The analysis of 2,341 comments showed that 89% of them expressed support and solidarity for press freedom, which was mostly expressed through the use of the hashtag #KamiTidakTakut. This study uses the Uses and Gratifications Theory to understand user motivations in interacting, including cognitive, affective, and social integration needs. The identified communication patterns are in accordance with the One-Step Flow Theory model, where messages from mass media are delivered directly to the audience without involving opinion leaders. Although mass media can influence individuals directly, the effects that arise from each individual can vary. These findings highlight the role of social media as a new digital public space that is effective in encouraging political participation, shaping public opinion, and expanding democracy amidst threats to press freedom. The implications of this research are expected to be a guide for media practitioners, academics, and policy makers in formulating adaptive communication strategies, as well as increasing media literacy and digital community participation in fighting for democratic values.Keywords: Virtual interaction, Social media, Terror Tempo 2025, Netnography, Uses and Gratifications, One-Step Flow Theory, Freedom of the press, Political participation, Media literacy, Digital democracy.